Structural features and surface composition of epitaxial α-FeSi2 films obtained by CVD. (5th January 2018) - Pushkarev, R.V.; Fainer, N.I.; Katsui, H.; Kaichev, V.V.; Goto, T.
Abstract: Iron disilicide (α-FeSi2 ) is one of the promising materials for building ohmic contacts over silicon substrates. Complex approaches have been used to synthesize this material resulting in the insufficient control of the film surface and interface structure. The morphology of the α-FeSi2 films synthesized in this work by one-step CVD technique from ferrocene varies from the highly-oriented self-assembled crystallites to the dense film of α-FeSi2 . The orientation of the material could be changed from α-FeSi2 (001)||Si(100) to α-FeSi2 (111)||Si(100) by raising the deposition temperature from 900 to 1000 °C. The epitaxial relationships FeSi2 (001)||Si(100), α-FeSi2 (010)||Si(001), and α-FeSi2 (111)||Si(100), α-FeSi2 (1 1 ¯ 0)||Si(011) were determined for both orientations by a pole figure technique. It was found the surface of the material has an iron oxide admixture. Both the surface and interface structure might have a great impact on the properties of the α-FeSi2 /Si structures. Graphical abstract: Highlights: Epitaxial α-FeSi2 self-assembled structures were deposited from ferrocene using chemical vapor deposition technique. The epitaxial orientation of α-FeSi2 structures depends on the deposition temperature. Morphology of the films changes from nanocrystallites to dense film depending on the deposition conditions. The surface of self-assembled structures is covered with thin layer of Fe2 O3 .